Development of a musculoskeletal model of the wrist to predict frictional work dissipated due to tendon gliding resistance in the carpal tunnel. Issue 9 (11th August 2021) - Glenday, J. D.; Steinhilber, B.; Jung, F.; Haeufle, D. F. B.
Abstract: Carpal tunnel syndrome is an entrapment neuropathy that has been associated with the aggravation of tendon gliding resistance due to forceful, high velocity, awkwardly angled, and repetitive wrist motions. Cadaveric and epidemiological studies have shown that combinations of these risk factors have a more than additive effect. The aim of the current study was to develop a musculoskeletal model of the wrist that could evaluate these risk factors by simulating frictional work dissipated due to the gliding resistance of the third flexor digitorum superficialis tendon. Three flexion angle zones, three extension angle zones, five levels of task repetitiveness, and five levels of task effort were derived from ergonomic standards. Of the simulations performed by systematically combining these parameters, the extreme wrist flexion zone, at peak task repetitiveness and effort, dissipated the most frictional work. This zone dissipated approximately double the amount of frictional work compared to its equivalent zone in extension. For all motions, a multiplicative effect of the combination of task repetitiveness and effort on frictional work was identified by the musculoskeletal model, corroborating previous epidemiological and experimental studies. Overall, these results suggest that the ergonomic standards for wrist flexion-extension may need to be adjusted to reflect equivalent biomechanical impact and that workplace tasks should be designed to minimise exposure to combinations of highly repetitive and highly forceful work, especially when the wrist is highly flexed.